The Influence of Organizational Commitment and Supervision on Discipline Through Job Satisfaction on Educational Personnel Faculty of Law, Brawijaya University, Malang - MEGAWATI, Fatmamia Putri; ROSIDI, Rosidi; MULYONO, Sugeng (PT Keberlanjutan Strategis Indonesia, 2023)
Organizational commitment is the relative strength of an individual's involvement in a particular organization, which is indicated by a strong belief in the goals and values of the organization, a willingness to make certain efforts for the benefit of the organization and a strong desire to continue being a member of the organization. This research aims to examine and analyze the influence of: i) organizational commitment to discipline, ii) supervision influences discipline, iii) organizational commitment to job satisfaction, iv) supervision to job satisfaction, v) job satisfaction to discipline, vi) organizational commitment to discipline through job satisfaction, vii) supervision of discipline through job satisfaction. This research was conducted at the Faculty of Law, Brawijaya University, Malang, using an explanatory research approach with a census sample technique obtained from 74 educational staff. Data was collected using a questionnaire method given directly to respondents. Then it was analyzed using path analysis.The results concluded that, all the proposed hypotheses were accepted, namely: (i) organizational commitment had an effect on discipline, (ii) supervision had an effect on discipline, (iii) organizational commitment had an effect on job satisfaction, (iv) supervision had an effect on job satisfaction, (v ) job satisfaction influences discipline, (vi) organizational commitment influences discipline through job satisfaction, (vii) supervision influences discipline through job satisfaction.